2021
DOI: 10.3390/ani11082448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex and Reproductive Status on Inhibitory Control and Social Cognition in the Domestic Dog (Canis familiaris)

Abstract: Sex differences in a variety of cognitive traits have long been reported in various species, including dogs. However, only a few canine studies have taken the possible effect of reproductive hormones into account. The aim of this study was to investigate the effects of sex and reproductive status of pet dogs (N = 1032) on two cognitive traits: inhibitory control and social cognition. Inhibitory control was assessed using the cylinder test, and the dogs’ tendency to initiate social contact with a human during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 85 publications
2
9
1
Order By: Relevance
“…Moreover, our estimate of between-study heterogeneity was low, suggesting that, even with small samples, we do not seem to have large sampling effects differing across studies. This is reassuring given the variation observed in dogs in breed, sex, and neuter status, some of which can influence impulsivity (Junttila et al, 2021(Junttila et al, , 2022. Nevertheless, as is often the case with meta-analyses (Valentine et al, 2010), we cannot draw strong conclusions and must call for more studies with larger sample sizes to address these questions.…”
Section: Limitationsmentioning
confidence: 93%
“…Moreover, our estimate of between-study heterogeneity was low, suggesting that, even with small samples, we do not seem to have large sampling effects differing across studies. This is reassuring given the variation observed in dogs in breed, sex, and neuter status, some of which can influence impulsivity (Junttila et al, 2021(Junttila et al, , 2022. Nevertheless, as is often the case with meta-analyses (Valentine et al, 2010), we cannot draw strong conclusions and must call for more studies with larger sample sizes to address these questions.…”
Section: Limitationsmentioning
confidence: 93%
“…Despite a number of studies reporting no sex differences in inhibitory control in dogs ( 13 , 19 , 22 ), a recent study ( 63 ) found that female dogs displayed better inhibitory control, making investigation of sex differences an interesting aspect for future research. In our study, the fact that the aggression test was performed first followed by two cognitive test on the same day may present a serious limitation.…”
Section: Discussionmentioning
confidence: 97%
“…An active area of research in human and rat impulsivity explores the mechanisms underlying this construct (Robbins & Dalley, 2017). Though studies of genetic (Hejjas et al, 2007;Kubinyi et al, 2012), neural (Cook et al, 2016), and hormonal (Rayment et al, 2020;Junttila et al, 2021) mechanisms of impulsivity are increasing in canine science, we lack a coherent research program on the underpinnings of impulsivity in dogs, and further investigations in this area could be a fruitful area of research (Olsen, 2018). Understanding the genetic, neural, and hormonal influences on impulsivity has critical implications for the breeding, selection, and training of not only pet dogs but also working and service dogs.…”
Section: Future Directionsmentioning
confidence: 99%